Weierstrass Representation for Minimal Surfaces into BCV-Spaces - Koivogui, M.; Todjihounde, L.; Kourouma, M. (Communications in Mathematics and Applications, 2013)
Bianchi-Cartan-Vranceanu spaces (BCV-spaces) are some 3-dimensional homogeneous manifolds equiped with a metric depending on 2 parameters $κ$ and $τ$, and whose isometries groups are of dimension four. In this paper, we describe a Weierstrass-type representation formula for simply connected minimal surfaces immersed into BCV-spaces.